Carbon network interface optimized sodium ion battery positive electrode material as well as preparation method and application thereof

By using oleic acid as a carbon source in the positive electrode material of sodium ion battery and introducing carbon nanotube modification, a conductive network is formed, and the low conductivity and uneven coating structure problems caused by phosphate ions are solved, achieving high specific capacity and excellent The rate performance is suitable for high-performance energy storage.

CN119252864APending Publication Date: 2025-01-03WUHAN SODIUM NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411563311.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The low electron conductivity and uneven carbon coating structure caused by phosphate ions of sodium ion batteries affect their electrochemical properties and sodium ion diffusion rate, making it difficult to meet the practical application needs.

Method used

Using oleic acid as the carbon source, and introducing carbon nanotube modifications during the material preparation process to form a conductive network, the sol-gel method is used to synthesize sodium ferrophosphate phosphate positive electrode material with a uniform carbon coating layer and a high specific surface area to improve the Conductivity and structural stability.

Benefits of technology

It significantly improves the conductivity and specific capacity of the material, shows excellent rate performance and cycle stability, is suitable for high-performance energy storage, and has the advantages of safety, environmental protection and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252864A_ABST
    Figure CN119252864A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon network interface optimized sodium ion battery positive electrode material, which is characterized in that ferric sodium pyrophosphate is used as a base material of the positive electrode material, and a carbon nanotube is filled between the base materials; the surface of the ferric sodium pyrophosphate base material is coated with an amorphous carbon layer, and the carbon content of the sodium ion battery positive electrode material is 1%-10%; and the specific surface area of the sodium ion battery positive electrode material is 20-25m < 2 > / g. According to the invention, oleic acid and the like are used as main carbon sources, carbon nanotubes are introduced to be inserted among positive electrode material particles, a sol-gel method is adopted to synthesize a precursor, and a finely controlled sintering process is adopted, so that the sodium ion battery positive electrode material with large specific surface area, rich pores and uniform carbon coating is successfully prepared, and the sodium ion battery positive electrode material shows relatively large capacity. The material shows excellent conductivity and structural stability. Compared with the existing positive electrode material, the material provided by the invention has higher ionic conductivity, has the advantages of safety, environmental protection and low cost, is suitable for the technical field of electrochemical energy storage batteries, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a carbon network interface optimized sodium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] The uneven distribution of lithium resources around the world and the low reserves have led to a surge in its price, which has seriously restricted the further application of lithium-ion batteries. Low-cost sodium-ion batteries (SIBs) are considered to be the most attractive candidates in the field of large-scale energy storage due to the abundant sodium reserves on the earth and similar electrochemical properties. Sodium-ion cathode materials occupy an important position in sodium-ion batteries. However, the large mass, large radius and slow movement speed of sodium ions have seriously hindered the application of sodium-ion batteries due to problems such as slow reaction kinetics, phase instability, low energy density and unsatisfactory reversibility of sodium ion insertion in electrode materials. Therefore, it is key to explore sodium-based materials with open framework structures and high structural stability, especially cathode materials. According to the current research status at home and abroad, the current cathode materials of sodium-ion batteries mainly include transition metal oxides, polyanionic compounds, metal hexacyanoacetic acid salts and organic compounds.

[0003] Among the many sodium-ion battery cathode materials, polyanion materials have attracted extensive attention due to their advantages such as high working potential, stable structural framework and good safety. Sodium-based polyanion materials are formed by polyanion polyhedra and transition metal polyhedra through strong covalent bonds and have a three-site network structure. Among them, sodium iron phosphate pyrophosphate (NFPP) not only has multidimensional ion diffusion channels, but also has a high voltage platform and excellent theoretical specific capacity, making it an environmentally friendly, low-cost and promising SIBs cathode material. However, NFPP also has inherent defects, such as phosphate ions that lead to low electronic conductivity of the material, hindering the diffusion rate of sodium ions and adversely affecting its electrochemical performance. At present, the conductivity of NFPP can be improved and the ion diffusion rate of the material can be increased by modification methods such as carbon coating, morphology adjustment, particle size reduction and interface modification. Although these methods have improved the electrochemical properties of the material to a certain extent, it is still difficult to fully meet the needs of practical applications. At the same time, traditional carbon sources such as sucrose and glucose often lead to uneven pore structure and inconsistent thickness of the carbon coating layer when preparing polyanion positive electrode materials, which in turn affects the electrochemical performance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carbon network interface optimized sodium ion battery positive electrode material and its preparation method and application, innovatively using oleic acid and the like as a carbon source, and introducing carbon nanotubes for modification to form a conductive network, achieving more uniform carbon coating in the material preparation process, greatly improving the conductivity and specific capacity of the material, and showing excellent rate performance and cycle stability.

[0005] In order to achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a carbon network interface optimized sodium ion battery positive electrode material, the positive electrode material uses sodium ferric phosphate pyrophosphate as a matrix material, and carbon nanotubes are filled between the matrix materials;

[0007] The surface of the sodium iron phosphate pyrophosphate matrix material is coated with an amorphous carbon layer, and the carbon content of the sodium ion battery positive electrode material is 1% to 10%;

[0008] The specific surface area of ​​the positive electrode material of the sodium ion battery is 20 to 25 m 2 / g.

[0009] As a preferred technical solution, the thickness of the amorphous carbon layer is 1 to 10 nm, preferably 3 to 4 nm.

[0010] As a preferred technical solution, the carbon content of the positive electrode material of the sodium ion battery is 3% to 5%.

[0011] The present invention also provides a method for preparing the carbon network interface optimized sodium ion battery positive electrode material, comprising the following steps:

[0012] (1) dissolving a carbon source and an iron source in anhydrous ethanol at a molar ratio of 1: (0.5-2), adding an appropriate amount of carbon nanotubes, and adding an appropriate amount of oxalic acid to prevent oxidation, and stirring and mixing at 30-80° C.; dissolving a sodium source and a phosphorus source in a stoichiometric ratio in ethanol respectively, and adding the solution to the ethanol solution containing the iron source and the carbon source, stirring for 1-3 hours to obtain a precursor solution, and adding deionized water to form a gel;

[0013] (2) drying the gel obtained in step (1) at 80-120° C. and grinding to obtain a precursor powder;

[0014] (3) calcining the precursor powder obtained in step (2) at 350-450° C. for 2-5 hours under an inert atmosphere to obtain a pre-carbonized material;

[0015] (4) Under an inert atmosphere, calcining the pre-carbonized material obtained in step (3) at 600-800° C. for 8-15 hours to obtain a positive electrode material for a sodium ion battery with an optimized carbon network interface.

[0016] Furthermore, in step (1), the carbon source is at least one of oleic acid, citric acid, oxalic acid, sucrose, glucose, amino sugar, starch, and phenolic resin.

[0017] Furthermore, in step (1), the iron source is at least one of ferrous oxalate and ferrous phosphate.

[0018] Furthermore, in step (1), the sodium source is at least one of sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, and sodium citrate.

[0019] Furthermore, in step (1), the phosphorus source is at least one of sodium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, sodium phosphate, and phosphoric acid.

[0020] Furthermore, in step (1), the molar concentration of the iron source in the precursor solution is 0.3-0.5 mol / L.

[0021] Furthermore, in step (1), the stoichiometric ratio of iron source: sodium source: phosphorus source is 1:(2-2.5):3.

[0022] Furthermore, in step (1), the amount of deionized water used is 5% to 10% of the volume of the precursor solution.

[0023] Furthermore, in steps (3) and (4), the gas used in the inert atmosphere is argon or nitrogen.

[0024] The present invention also provides application of the carbon network interface optimized sodium ion battery positive electrode material in sodium batteries.

[0025] The present invention uses oleic acid and the like as the main carbon source, introduces carbon nanotubes interspersed between the positive electrode material particles, adopts the sol-gel method to synthesize the precursor, and through a finely controlled sintering process, successfully prepares a sodium ion battery positive electrode material with a large specific surface area, rich pores, and uniform carbon coating, showing a large capacity. The preparation method includes mixing a carbon source, an iron source, a sodium source, and a phosphorus source in proportion to form a uniform precursor colloid, and finally obtaining a sodium ion battery positive electrode material with a carbon network modified structure through the steps of drying and sintering. The material exhibits excellent electrical conductivity and structural stability. Compared with existing positive electrode materials, the material of the present invention has higher ion conductivity, and has the advantages of safety, environmental protection, and low cost. It is suitable for the field of electrochemical energy storage battery technology and has broad application prospects.

[0026] The present invention combines morphology adjustment and interface treatment to further improve the conductivity and ion transmission efficiency of NFPP materials, so as to better meet the application requirements of sodium ion batteries in the field of high-performance energy storage. The carbon network interface optimized sodium ion battery positive electrode material of the present invention exhibits excellent rate performance and cycle stability in different types of electrochemical energy storage devices.

[0027] The present invention relates to a sodium iron pyrophosphate material prepared by optimizing the carbon network interface and its application in sodium batteries. By combining in-situ carbon network interface optimization with a sol-gel method, the present invention prepares a carbon-coated sodium iron pyrophosphate material with a large specific surface area and a uniform particle distribution, with oleic acid and the like as the main carbon source, and with oleic acid and the like as the main carbon source. The material has a uniform carbon coating layer and good structural stability, and exhibits excellent capacity, rate performance and cycle stability. Compared with other conversion-type positive electrode materials, the sodium iron pyrophosphate positive electrode material optimized by the in-situ carbon network interface has a good conductive skeleton, and with oleic acid and the like as the main carbon source, the uniform carbon coating structure formed further improves the capacity and conductivity of the material, the amorphous product can be better dispersed in the conductive skeleton, the structural stability is high, and the generated phosphate has good sodium ion conductivity, which can accelerate the transmission of sodium ions, so that the positive electrode material exhibits excellent rate performance and cycle performance, and has broad application prospects in high-performance power batteries and electrochemical energy storage battery technologies.

[0028] The sodium iron pyrophosphate material with optimized carbon network interface was successfully prepared by combining in-situ carbon network interface optimization and sol-gel method. Compared with other conversion-type positive electrode materials, the sodium iron pyrophosphate positive electrode material with optimized in-situ carbon network interface has a good conductive skeleton, and its amorphous product can be better dispersed in the conductive skeleton, with good structural stability. The generated phosphate has good sodium ion conductivity, which can accelerate the transmission of sodium ions, so that the sodium iron pyrophosphate positive electrode material exhibits excellent rate performance and cycle performance, and has broad application prospects in high-performance power batteries and electrochemical energy storage battery technologies. The material of the present invention not only exhibits excellent performance in sodium ion batteries, but also has broad application prospects. Its three-dimensional structure and large specific surface area enable it to provide continuous and reliable power supply in flexible electronic devices, improve the cruising range and accelerate the charging process in electric vehicles. These characteristics further highlight the innovativeness and practical application value of the present invention.

[0029] In terms of preparation method, the modification method of the present invention is simple, easy to operate, low in cost, and has obvious effect, and has industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the sodium ferric pyrophosphate with optimized carbon network interface prepared by the sol-gel method in Example 1.

[0031] Figure 2 This is the SEM image of the carbon-coated sodium iron pyrophosphate prepared by the sol-gel method in Comparative Example 1.

[0032] Figure 3 TEM image of sodium ferric pyrophosphate with optimized carbon network interface prepared by the sol-gel method in Example 1.

[0033] Figure 4 BET test of sodium iron pyrophosphate with optimized carbon network interface prepared by sol-gel method in Example 1.

[0034] Figure 5 This is the first charge and discharge curve of the sodium iron pyrophosphate with optimized carbon network interface in Example 1.

[0035] Figure 6 This is the first charge and discharge curve of the carbon-coated sodium iron pyrophosphate in Comparative Example 1.

[0036] Figure 7 This is the cyclic voltammetry curve of sodium iron pyrophosphate with optimized carbon network interface in Example 1. DETAILED DESCRIPTION

[0037] The specific implementation modes of the present invention will be described clearly and completely below with reference to the accompanying drawings.

[0038] Obviously, the described embodiments are only used to explain the present invention, and are not used to limit the present invention. Those skilled in the art may make some non-essential changes and adjustments based on the contents of the present invention, which all fall within the protection scope of the present invention.

[0039] The carbon network interface optimized sodium ion battery positive electrode material is mixed with a conductive agent and a binder to prepare an electrode slurry, which is evenly coated on the current collector, dried, rolled and cut into pieces to obtain the sodium battery positive electrode sheet, which is then assembled into a battery cell with a commercial negative electrode sheet and injected with an electrolyte to make a sodium ion battery.

[0040] During the preparation process, the conductive agent may be one or more of Super P, acetylene black, carbon nanotubes, graphene, etc.; the binder may be one or more of PVDF, PTFE, CMC+SBR, etc.; the current collector may be one or more of aluminum foil, copper foil, stainless steel mesh, nickel foil, titanium foil, etc.; the solute of the electrolyte may be one or more of NaSO4, NaNO3, CH3COONa, NaF6, NaClO4, NaOH, NaCl, NaH2PO4, NaBr, NaCO3; the solvent of the electrolyte is an organic solvent.

[0041] The present invention is further described below in conjunction with embodiments and drawings.

[0042] Example 1

[0043] A method for preparing a positive electrode material for a sodium ion battery with a carbon network interface optimization comprises the following steps:

[0044] (1) dissolving oleic acid and ferrous oxalate in anhydrous ethanol at a molar ratio of 1:1, adding carbon nanotubes (controlling the carbon content of the positive electrode material of the sodium ion battery to be 5%), and adding an appropriate amount of oxalic acid to prevent oxidation, and stirring and mixing at 70°C; dissolving sodium dihydrogen phosphate and ammonium dihydrogen phosphate in stoichiometric ratios in ethanol respectively, and adding them to the ethanol solution containing the iron source and the carbon source, stirring for 3 hours to obtain a precursor solution, the molar concentration of the iron source in the precursor solution is 0.3 mol / L, and gel is formed after adding deionized water, and the amount of deionized water used is 5% of the volume of the precursor solution;

[0045] Among them, the stoichiometric ratio of iron source: sodium source: phosphorus source is 1:2:3;

[0046] (2) drying the gel at 80° C. and grinding to obtain a precursor powder;

[0047] (3) calcining the precursor powder at 350° C. for 4 hours under an argon atmosphere to obtain a pre-carbonized material;

[0048] (4) Under an argon atmosphere, the pre-carbonized material was calcined at 750°C for 15 hours to obtain a carbon network interface optimized sodium ion battery positive electrode material.

[0049] Battery test: The obtained active material, conductive carbon black (SuperP), and binder (PVDF) are dissolved in an appropriate amount of N-methylpyrrolidone solvent at a mass ratio of 8:1:1, mixed, and coated with a scraper to form an electrode film with a thickness of 0.08 mm. After vacuum drying, the electrode film is cut into an electrode sheet with a diameter of 14 mm using a slicer, and the mass of the active material is weighed and calculated. At the same time, a sodium sheet is used as the negative electrode, a glass fiber diaphragm is used as the diaphragm, and a 1mol / LNaClO4 (EC:DEC=1:1) solution is used as the electrolyte. A button cell is assembled in an argon-filled glove box, and the assembled battery is then subjected to charge and discharge tests. The preparation of the electrode and the battery assembly process are prior art, and this application will not repeat them.

[0050] from Figure 1 It can be seen that the sample synthesized in Example 1 introduces carbon nanotubes interspersed between the positive electrode material particles, and its specific surface area is large, the pores are rich, and the carbon coating is uniform. The positive electrode material of the sodium ion battery is obtained by carbon network modification-carbon coating.

[0051] from Figure 3 It can be seen that the sample synthesized in Example 1 is uniformly coated with an amorphous carbon layer with a thickness of 3.2 nm, which can not only limit the excessive growth of primary particles and improve the electronic conductivity of the sample, but also prevent the electrode sheet from being corroded by the electrolyte.

[0052] from Figure 4It can be seen that the sample synthesized in Example 1 shows a three-dimensional structure with a conductive network formed, and the specific surface area can reach 21.6m 2 / g, effectively improving the capacity and sodium ion conductivity of the material. It is beneficial to the transport of ions and the full wetting of the electrode sheet by the electrolyte, ensuring a large contact area between the electrode material and the electrolyte.

[0053] from Figure 5 It can be seen that the charge and discharge curve of the first cycle of the sodium ion battery assembled in Example 1 has a discharge specific capacity of 108.7 mAh / g.

[0054] from Figure 7 It can be seen that the cyclic voltammetry (CV) method was used at a scan rate of 0.4 mV s -1 Under the condition of 1.5V~4.2V(vs.Na / Na + ) The electrochemical performance of the embodiment was tested by constant current charge and discharge within the potential range. There was no significant difference in the cyclic voltammetry curves of the first five cycles, indicating that the structure of the electrode material achieved stable insertion and extraction of sodium ions.

[0055] The test results of Example 1 show that the prepared carbon-coated sodium ion battery positive electrode material has rich pores and a specific surface area of ​​21.6 m 2 / g, significantly better than the commercially available sodium iron pyrophosphate material, and evenly coated with a 3.2nm thick amorphous carbon layer. Under 1C conditions, the discharge capacity is as high as 108.7mAh / g.

[0056] Example 2

[0057] Properties of materials at different calcination temperatures.

[0058] (1) dissolving oleic acid and ferrous oxalate in anhydrous ethanol at a molar ratio of 1:1, adding carbon nanotubes (controlling the carbon content of the positive electrode material of the sodium ion battery to be 5%), and adding an appropriate amount of oxalic acid to prevent oxidation, and stirring and mixing at 70°C; dissolving sodium dihydrogen phosphate and ammonium dihydrogen phosphate in stoichiometric ratios in ethanol respectively, and adding them to the ethanol solution containing the iron source and the carbon source, stirring for 3 hours to obtain a precursor solution, the molar concentration of the iron source in the precursor solution is 0.3 mol / L, and gel is formed after adding deionized water, and the amount of deionized water used is 5% of the volume of the precursor solution;

[0059] Among them, the stoichiometric ratio of iron source: sodium source: phosphorus source is 1:2:3;

[0060] (2) drying the gel at 80° C. and grinding to obtain a precursor powder;

[0061] (3) calcining the precursor powder at 350° C. for 4 hours under an argon atmosphere to obtain a pre-carbonized material;

[0062] (4) Under an argon atmosphere, the pre-carbonized material was calcined at 650°C for 15 hours to obtain a carbon network interface optimized sodium ion battery positive electrode material.

[0063] Battery test: The obtained active material, conductive carbon black (SuperP), and binder (PVDF) were dissolved in an appropriate amount of N-methylpyrrolidone solvent at a mass ratio of 8:1:1, and then coated with a scraper to form an electrode film with a thickness of 0.08 mm. After vacuum drying, they were cut into electrode sheets with a diameter of 14 mm using a slicer, and the mass of the active material was weighed and calculated. At the same time, a sodium sheet was used as the negative electrode, a glass fiber diaphragm was used as the diaphragm, and a 1mol / LNaClO4 (EC:DEC=1:1) solution was used as the electrolyte. A button cell was assembled in an argon-filled glove box, and the assembled battery was then subjected to charge and discharge tests. The test results of Example 2 show that under 1C conditions, the discharge specific capacity is 93.3mAh / g.

[0064] Example 3

[0065] Properties of materials prepared under different stoichiometric ratios of raw materials.

[0066] (1) dissolving oleic acid and ferrous oxalate in anhydrous ethanol at a molar ratio of 1:1, adding carbon nanotubes (controlling the carbon content of the positive electrode material of the sodium ion battery to be 5%), and adding an appropriate amount of oxalic acid to prevent oxidation, and stirring and mixing at 70°C; dissolving sodium dihydrogen phosphate and ammonium dihydrogen phosphate in stoichiometric ratios in ethanol respectively, and adding them to the ethanol solution containing the iron source and the carbon source, stirring for 3 hours to obtain a precursor solution, the molar concentration of the iron source in the precursor solution is 0.3 mol / L, and gel is formed after adding deionized water, and the amount of deionized water used is 5% of the volume of the precursor solution;

[0067] Among them, the stoichiometric ratio of iron source: sodium source: phosphorus source is 1:2.5:3;

[0068] (2) drying the gel at 80° C. and grinding to obtain a precursor powder;

[0069] (3) calcining the precursor powder at 350° C. for 4 hours under an argon atmosphere to obtain a pre-carbonized material;

[0070] (4) Under an argon atmosphere, the pre-carbonized material was calcined at 750°C for 15 hours to obtain a carbon network interface optimized sodium ion battery positive electrode material.

[0071] Battery test: The obtained active material, conductive carbon black (SuperP), and binder (PVDF) were dissolved in an appropriate amount of N-methylpyrrolidone solvent at a mass ratio of 8:1:1, and then coated with a scraper to form an electrode film with a thickness of 0.08 mm. After vacuum drying, they were cut into electrode sheets with a diameter of 14 mm using a slicer, and the mass of the active material was weighed and calculated. At the same time, a sodium sheet was used as the negative electrode, a glass fiber diaphragm was used as the diaphragm, and a 1mol / LNaClO4 (EC:DEC=1:1) solution was used as the electrolyte. A button cell was assembled in an argon-filled glove box, and the assembled battery was then subjected to charge and discharge tests. The test results of Example 2 show that under 1C conditions, the discharge specific capacity is 85.6mAh / g.

[0072] Comparative Example 1

[0073] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:

[0074] (1) dissolving oleic acid and ferrous oxalate in anhydrous ethanol at a molar ratio of 1:1, adding an appropriate amount of oxalic acid to prevent oxidation, and stirring and mixing at 70°C to uniformly obtain the mixture; dissolving sodium dihydrogen phosphate and ammonium dihydrogen phosphate in ethanol in a stoichiometric ratio respectively, and adding the mixture to an ethanol solution containing an iron source and a carbon source, stirring for 3 hours to obtain a precursor solution, wherein the molar concentration of the iron source in the precursor solution is 0.3 mol / L, and adding deionized water to form a gel, wherein the amount of deionized water used is 5% of the volume of the precursor solution; wherein the stoichiometric ratio of the iron source: the sodium source: the phosphorus source is 1:2:3;

[0075] (2) drying the gel at 80° C. and grinding to obtain a precursor powder;

[0076] (3) calcining the precursor powder at 350° C. for 4 hours under an argon atmosphere to obtain a pre-carbonized material;

[0077] (4) Under an argon atmosphere, the pre-carbonized material was calcined at 750°C for 15 hours to obtain a carbon network interface optimized sodium ion battery positive electrode material.

[0078] Battery test: The obtained active material, conductive carbon black (SuperP), and binder (PVDF) are dissolved in an appropriate amount of N-methylpyrrolidone solvent at a mass ratio of 8:1:1, mixed, and coated with a scraper to form an electrode film with a thickness of 0.08 mm. After vacuum drying, the electrode film is cut into an electrode sheet with a diameter of 14 mm using a slicer, and the mass of the active material is weighed and calculated. At the same time, a sodium sheet is used as the negative electrode, a glass fiber diaphragm is used as the diaphragm, and a 1mol / LNaClO4 (EC:DEC=1:1) solution is used as the electrolyte. A button cell is assembled in an argon-filled glove box, and the assembled battery is then subjected to charge and discharge tests. The preparation of the electrode and the battery assembly process are prior art, and this application will not repeat them.

[0079] from Figure 2 It can be seen that the particles of the sample synthesized in the comparative example exhibit a larger size, about 1 μm.

[0080] from Figure 6 It can be seen that the charge and discharge curve of the first cycle of the sodium ion battery assembled in the embodiment has a discharge specific capacity of 96.7 mAh / g.

[0081] In order to ensure that the above are only preferred embodiments of the present invention, only the implementation methods of the present invention are described, and the patent scope of the present invention is not limited thereby. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly used in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A carbon network interface optimized sodium ion battery positive electrode material, characterized in that: The positive electrode material uses sodium iron phosphate pyrophosphate as a matrix material, and carbon nanotubes are filled between the matrix materials; The surface of the sodium iron phosphate pyrophosphate matrix material is coated with an amorphous carbon layer, and the carbon content of the sodium ion battery positive electrode material is 1% to 10%; The specific surface area of ​​the positive electrode material of the sodium ion battery is 20 to 25 m 2 / g.

2. The carbon network interface optimized sodium ion battery positive electrode material according to claim 1, characterized in that: The thickness of the amorphous carbon layer is 1-10 nm.

3. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The following steps are involved: (1) dissolving a carbon source and an iron source in anhydrous ethanol at a molar ratio of 1: (0.5-2), adding an appropriate amount of carbon nanotubes, and adding an appropriate amount of oxalic acid to prevent oxidation, and stirring and mixing at 30-80° C.; dissolving a sodium source and a phosphorus source in a stoichiometric ratio in ethanol respectively, and adding the solution to the ethanol solution containing the iron source and the carbon source, stirring for 1-3 hours to obtain a precursor solution, and adding deionized water to form a gel; (2) drying the gel obtained in step (1) at 80-120° C. and grinding to obtain a precursor powder; (3) calcining the precursor powder obtained in step (2) at 350-450° C. for 2-5 hours under an inert atmosphere to obtain a pre-carbonized material; (4) Under an inert atmosphere, calcining the pre-carbonized material obtained in step (3) at 600-800° C. for 8-15 hours to obtain a positive electrode material for a sodium ion battery with an optimized carbon network interface.

4. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 3, characterized in that: In step (1), the carbon source is at least one of oleic acid, citric acid, oxalic acid, sucrose, glucose, amino sugar, starch, and phenolic resin; The iron source is at least one of ferrous oxalate and ferrous phosphate.

5. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 3, characterized in that: In step (1), the sodium source is at least one of sodium hydroxide, sodium acetate, sodium nitrate, sodium oxalate, and sodium citrate; The phosphorus source is at least one of sodium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, sodium phosphate, and phosphoric acid.

6. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 3, characterized in that: In step (1), in step (1), the molar concentration of the iron source in the precursor solution is 0.3 to 0.5 mol / L.

7. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 3, characterized in that: In step (1), the stoichiometric ratio of iron source: sodium source: phosphorus source is 1: (2-2.5):

3.

8. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 3, characterized in that: In step (1), the amount of deionized water used is 5% to 10% of the volume of the precursor solution.

9. The method for preparing the carbon network interface optimized sodium ion battery positive electrode material according to claim 3, characterized in that: In steps (3) and (4), the gas used in the inert atmosphere is argon or nitrogen.

10. Use of the carbon network interface optimized sodium ion battery positive electrode material according to any one of claims 1 to 9 in sodium batteries.

Citation Information

Patent Citations

  • Preparation method of lithium iron phosphate and carbon nano tube composite material for lithium ion battery

    CN102916182A

  • Polyanionic sodium ion battery positive electrode material and preparation method thereof

    CN110226252A

  • Sodium ferric phosphate-coated carbon nanotube positive electrode material with low iron-phosphorus ratio and preparation method of sodium ferric phosphate-coated carbon nanotube positive electrode material

    CN114843432A

  • Carbon-coated sodium ferric pyrophosphate positive electrode material, preparation method thereof and sodium ion battery

    CN117438560A

  • Polyanionic sodium ion battery anode material and preparation method thereof

    WO2020019311A1

Cited By

  • Quickly synthesized ferric sodium pyrophosphate electrode material, preparation method thereof and positive electrode

    CN121202094A